Binary Particle Swarm Optimization Algorithm for Euclidean Steiner Tree - Cao, Shuxian; Chen, Jingrong; Gou, Jiaojiao (2024 4th International Conference on Computer Science and Blockchain (CCSB), 2024)
The Euclidean Steiner tree problem is a well-known combinatorial optimization problem and also an NP hard problem. This article focuses on the problem of using Euclidean distance to solve the Steiner tree problem using binary particle swarm optimization algorithm. The algorithm first extracts the selected Steiner points from the global optimal solution and converts them into corresponding original node numbers. Then use binary encoding to indicate whether each particle has selected the corresponding Steiner point. Finally, the effectiveness and feasibility of the algorithm were verified through the problem of setting up a communication network, and the test results showed that the algorithm has good solving performance.